Nontrivial Solutions for Time Fractional Nonlinear Schrödinger-Kirchhoff Type Equations - N. Nyamoradi; Y. Zhou; E. Tayyebi; B. Ahmad; A. Alsaedi (Discrete Dynamics in Nature and Society)
We study the existence of solutions for time fractional Schrödinger-Kirchhoff type equation involving left and right Liouville-Weyl fractional derivatives via variational methods.